Three-Dimensional CT Findings of Os Calcaneus Secundarius Mimicking a Fracture - Mehmet Deniz Bulut; Alpaslan Yavuz; Aydın Bora; Mehmet Ata Gökalp; Sercan Özkaçmaz; Abdussamet Batur (Case Reports in Radiology)
Os calcaneus secundarius is one of several accessory ossicles of the foot that have been identified as normal variants of skeletal development. It may cause ankle pain and may mimic an avulsion fracture of the anterior calcaneal process. A twenty-year-old male was admitted to our institution with right ankle pain following an inversion injury. An axial CT image of the patient’s right ankle revealed a shape with smooth and sharp margins, identified as a well-corticated bone fragment in the subtalar region. A diagnosis of an accessory ossicle, os calcaneus secundarius, was made based on radiographic findings. As a result of this case, it is recommended that potential locations of the accessory bones should be well understood in order to prevent misdiagnosis and inappropriate surgical procedures. Os calcaneus secundarius must be considered when an apparent bone fragment or a suspicious fracture line at the anterior region of os calcaneus is demonstrated.